Did internet use protect older adults’ mental health during the COVID-19 pandemic? : It depends on their pre-pandemic social connectedness - Settels, Jason; Bertogg, Ariane (My University, 2025)
Many studies have addressed changes in mental health during the COVID-19 pandemic's early lockdown stage. Fewer studies have investigated the further developments in older adults' mental health throughout the pandemic's later stages. Research gaps particularly pertain to the role of how online information search behaviour and offline social network interact. Both provide important resources (e.g., information, support, services) that are essential for independence and well-being in later life. By investigating how they interact, we propose four theoretically derived mechanisms and test them using high-quality data. Based on the Survey of Health, Ageing and Retirement in Europe's (SHARE) wave eight (2019) and second Corona survey (May–September 2021), we apply multinomial logistic regressions to predict stability and increase of depressive mood between the first and the second pandemic phases among 30,076 adults aged 50 years or older, observed in 27 countries. Results show that increased government information search online is associated with increased depressive mood. Pre-pandemic social connectedness moderates the associations between internet use and depressive mood positively, decreasing the risk of depressive mood among internet non-users and pointing to compensation of lacking online resources via offline social ties. Additionally, the negative effects of increased government information search were aggravated by deeper social connectedness, pointing to conflicts or disagreements over pandemic governance policy that may arise in close social networks.
Keywords: 300